Kepuasan Pelayanan Pendidikan: Studi pada Program Studi Terapan Kepelatihan Olahraga Universitas Negeri Surabaya - Fajar, Muhammad Kharis; Ashadi, Kunjung; Sidik, Rizky Muhammad; Rusdiawan, Afif; Rasyid, Muhammad Labib Siena Ar (STKIP Muhammadiyah Kuningan, 2023)
University, which is the only vocational education program in sports in Indonesia. This study used quantitative survey research with 47 undergraduate students of Applied Sports Coaching at Surabaya State University as research subjects. The instrument used uses the SERVQUAL method, which consists of five dimensions, reliability, responsiveness, assurance, empathy, and tangible, with 22 questions. The research questionnaire is given online when students make a study plan. The results showed that the Customer Satisfaction Index (CSI) value was 66.58%. The dimensions of responsibility and credibility are the best compared to the other dimensions. The conclusion is that overall the level of satisfaction with educational services felt by students at the Bachelor of Applied Sports Coaching at Surabaya State University is in the satisfied category. However, some dimensions need to be improved, namely, transparency and fairness.